Pengembangan Sentra Produksi Kain Tenun Tedunan sebagai Upaya Membangun Perekonomian Desa Tedunan yang Berkelanjutan - Cahyo Wulandari; Matus Hanun Az Zahra (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
edunan is one of the villages that produce woven fabrics in Indonesia. Woven fabric is a textile product that is listed as the original intangible cultural heritage of Indonesia. Woven fabrics are generally known as Indonesia’s local cultural wisdom, woven fabrics also become Indonesia's export products that have high economic value. However, despite its potential, it turns out that the Tedunan’s woven fabric business faced serious problems. One of the bigger issues in developing Tedunan’s woven business is the trend of fast fashion products. The existence of this trend has an impact on the declining interest of the Indonesian people to buy local clothing products such as woven and batik. Furthermore, the existence of garment and textile factories around Tedunan Village gave an impact on reducing interest of youth to become woven craftsmen. This case becomes worse because the potential of Tedunan’s woven fabrics will become extinct due to the lack of regeneration of woven craftsmen. Therefore, the existence of this research program aims to help Tedunan woven cloth craftsmen in developing their business. In addition, this program aims to provide analysis and recommendations in building the Tedunan’s Woven business centre by developing synergy and collaboration as an effort to achieve a sustainable economy. Data collection in this study was carried out by observation and in-depth interviews with the Tedunan’s Woven craftsmans and village governments to find out the root of these problems. There are four main problems in the Tedunan’s woven business, such as lack of capital, production, marketing, and regeneration. Therefore, the programs are designed on answering all existing problems, such as a program for mapping the potential and problems of the Tedunan’s woven business, preparing a roadmap for policy recommendations, program for making documentary videos, and digital marketing workshop. All of these programs are purposed to provide insight to the community about steps to develop the Tedunan’s woven fabric business so that it can impact toward the social and economic well-being in the long term.